E-governance in India: Problems, challenges and opportunities - A futures vision - Dey, Bata K. (2000)
Focusing on present status and future potential of e-governance in India, the author analyses some of the serious problems and challenges that confront implementation of e-governance in India. He also discusses in the process its tremendous potentialities, some of which are getting reflected in the provisions made in IT ACT 2000. He then examines the present status of IT revolution and the promises it holds for the future generations as far as giving better deal to the people, realising positive values in administration, etc., are concerned, before concluding the discussion. - Reproduced
Keywords: E governance - India; Information technology - India; E governance